2020
DOI: 10.1111/jth.14665
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fibrinogen concentrate in major abdominal surgery – A prospective, randomized, controlled study in cytoreductive surgery for pseudomyxoma peritonei

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. AbstractBackground: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy for pseudomyxoma peritonei (PMP) is associated with excessive bleeding and acquired fibrinogen deficiency. Maintaining plasma fibrinogen may support hemostasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(81 citation statements)
references
References 37 publications
4
73
0
4
Order By: Relevance
“…A recently published randomized controlled trial (RCT) comparing the use of FC vs cryoprecipitate for bleeding control in major abdominal surgery observed that all TEEs occurred in the cryoprecipitate group, while no TEE was observed in the FC group. 4 In addition, the FIBRES randomized study in 735 cardiac surgery patients that compared FC to cryoprecipitate found a trend toward more TEE in the cryoprecipitate treated patients. 5 Finally, this review article uses the terms systematic review and meta-analysis in the Methods section, but does not coherently follow guidelines for this type of analysis.…”
Section: Response To Wirtz Et Al: the Impact Of Blood Product Ratio Amentioning
confidence: 99%
“…A recently published randomized controlled trial (RCT) comparing the use of FC vs cryoprecipitate for bleeding control in major abdominal surgery observed that all TEEs occurred in the cryoprecipitate group, while no TEE was observed in the FC group. 4 In addition, the FIBRES randomized study in 735 cardiac surgery patients that compared FC to cryoprecipitate found a trend toward more TEE in the cryoprecipitate treated patients. 5 Finally, this review article uses the terms systematic review and meta-analysis in the Methods section, but does not coherently follow guidelines for this type of analysis.…”
Section: Response To Wirtz Et Al: the Impact Of Blood Product Ratio Amentioning
confidence: 99%
“…In the FIBRES trial comparing fibrinogen concentrate to cryoprecipitate in adult cardiac surgery patients, the investigators found a non‐significant trend towards a lower risk of arterial and venous thromboembolic complications with fibrinogen concentrates as compared to cryoprecipitate (odds ratio 0.70, 95% confidence interval 0.42‐1.20). In a randomized trial of fibrinogen concentrates versus cryoprecipitate in patients undergoing abdominal surgery for pseudomyxoma peritonei, the observed thrombosis rate was higher in the cryoprecipitate arm (7/23–30.4%) versus the fibrinogen concentrate arm (0/22–0%) . The overall risk of thrombosis for patients who receive fibrinogen concentrate is most likely extremely low; a recent review of randomized controlled trials that included over 700 patients who received fibrinogen concentrate summarized that no study reported an increase in the rate of perioperative thrombosis in the fibrinogen versus comparator arms …”
Section: Pro Fibrinogen Concentrate: Fibrinogen Concentrate Is the Prmentioning
confidence: 99%
“…In a randomized trial of fibrinogen concentrates versus cryoprecipitate in patients undergoing abdominal surgery for pseudomyxoma peritonei, the observed thrombosis rate was higher in the cryoprecipitate arm (7/23-30.4%) versus the fibrinogen concentrate arm (0/22-0%). 9 The overall risk of thrombosis for patients who receive fibrinogen concentrate is most likely extremely low; a recent review of randomized controlled trials that included over 700 patients who received fibrinogen concentrate summarized that no study reported an increase in the rate of perioperative thrombosis in the fibrinogen versus comparator arms. 5…”
Section: Recipient Safetymentioning
confidence: 99%
“…In terms of safety, they also appear similar, although cryoprecipitate may be associated with a higher risk of thromboembolic complications. 2,4 There are three areas of active research related to fibrinogen replacement. First, only two trials have been performed to determine the most effective dosing strategy (e.g., fixed dose vs. weight based vs. targeted to a postinfusion fibrinogen level): an RCT in postpartum hemorrhage found no impact of 2 g of fibrinogen, suggesting the minimum required dose is more than 2 g, and a trial in major pediatric surgery found earlier dosing of fibrinogen concentrate (at a higher FIBTEM maximum clot firmness threshold) was more effective in reducing transfusion requirements.…”
Section: Fibrinogen Concentratementioning
confidence: 99%
“…Randomized controlled trials (RCTs) comparing fibrinogen concentrate to cryoprecipitate for the management of adult cardiac surgery, pediatric cardiac surgery and abdominal cancer surgery confirm equivalent hemostatic efficacy of fibrinogen concentrate and cryoprecipitate. In terms of safety, they also appear similar, although cryoprecipitate may be associated with a higher risk of thromboembolic complications . There are three areas of active research related to fibrinogen replacement.…”
Section: Fibrinogen Concentratementioning
confidence: 99%